Centralna surowicza choroidoretinopatia – diagnostyka, monitorowanie i leczenie - Siwiec-Prościńska, Joanna; Prościnski, Tomasz; Kocięcki, Jarosław; Pecold, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
There are many clinical forms of central serous choroidoretinopathy (CSCR) with different prognosis. Although fluoresceine angiography still plays the most important role in the diagnosis of CSCR, it should be pointed out, that examination with retinal thickness analyser and optical coherent tomography is a modern and non-invasive method of retinal examination, which can provide with some significant and reliable observations helping in objective monitoring of CSCR. The aim of this paper was the description of diagnostic methods and analysis of optimal methods used for monitoring of CSCR. Because the research of the literature suggests, that local: nonsteroid anti-inflammatory drugs, ß-blockers and systemic or local carbonic anhydrase inhibitors may be helpful in therapeutic choice, the treatment options of CSCR were also analysed.